Tendency to Ingest Foreign Bodies in Mentally Retarded Patients: A Case with Ileal Perforation Caused by the Ingestion of a Teaspoon - İhsan Yıldız; Yavuz Savaş Koca; Gökhan Avşar; İbrahim Barut (Case Reports in Surgery)
Introduction. Unintentional foreign body ingestion commonly occurs accidentally in children aged between 3 months and 6 years and at advanced ages or results from psychiatric disorders such as hallucination in patients with mental retardation. Most of the ingested foreign bodies are naturally discharged from the body but some of them may require surgical intervention. Presentation of Case. A 29-year-old mentally retarded female patient was admitted to the emergency service with a two-day history of abdominal pain, nausea, and vomiting. Physical examination revealed abdominal tenderness, defense, and rebound on palpation. Radiological examination revealed diffuse air-fluid levels and a radiopaque impression of a metal object in the right upper quadrant. The metal teaspoon causing ileal perforation was extracted by emergency laparotomy. On postoperative day 7, the patient was uneventfully discharged following a psychiatric consultation. Discussion. Foreign body ingestion can occur intentionally in children at developing ages and old-age patients, or adults and prisoners, whereas it may occur unintentionally in patients with mental retardation due to hallucination. However, repeated foreign body ingestion is very rare in individuals other than mentally retarded patients. Conclusion. Mentally retarded patients should be kept under close surveillance by surgeons and psychiatrists due to their tendency to ingest foreign bodies.